Driving Factors Of Employee Performance Inspiration Auto2000 Pasteur - Nisita, Arva Kyla; Firmansyah, Yayan; Sutisna, Mamun (Eqien - Jurnal Ekonomi dan Bisnis, 2024)
Based on the observations and preliminary survey on the research object, it was hypothesized that the main driving factor for employee performance is compensation. This study aims to determine the effect of compensation on employee performance at Auto2000 Pasteur Bandung. This study used quantitative methods that are causal and used primary data whose data collection used questionnaires with the calculation of results using the Likert scale with a scale of numbers 1-5. The technique used in sampling uses non-probability sampling with census sampling techniques. The population in this study was 68 Auto2000 Pasteur employees and the same number of samples. Data analysis method using Smart PLS. Data that have been obtained from questionnaires and have been tabulated are then analyzed using validity reliability tests, R2 tests, hypothesis tests, and partial tests (t-tests). The results showed that compensation significantly positively affected the performance of employees of the company Auto2000 Pasteur.